Influencia del porcentaje de quitosano en la calidad física y microbiológica del banano en poscosecha Calceta-Ecuador - Uscocovich Álvarez, Ángel Alberto (2021)
The objective of the present study was to evaluate the effect of different percentages of chitosan on the physical and microbiological quality of banana post harvest. Afterwards, for the preparation of the coating, different percentages of chitosan (0.75 %, 1.00%, 1.25 %, 1.50 % w/v) of 95 % in degree of deacetylation in its composition plus a control were used. The percentage of weight loss was evaluated, content of total soluble solids (°Brix), skin color during ripening, instrumental firmness and microbiological count were evaluated. A completely randomized block design (DBCA) was performed, with five treatments and five blocks corresponding to initial day zero, day five, day ten, day 15 and day 20 of storage. Bananas reported permanent weight loss, with 1.25 % chitosan treatment standing out with the least loss. Regarding the content of SST (°Brix), it gradually increased, indicating an acceleration in the banana maturity index. The samples coated with 1.50 % chitosan reported a lower content with 13.65 °Brix and the highest rigidity in the fruit, a maximum penetration force of 10.33 N was reported in addition to the lower microbiological content recorded. The fruit coated with 1.25 % chitosan presented the best results with less weight loss, while 1.50 % chitosan in the coating reported lower content of °Brix, lower luminosity of 54.27, greater instrumental firmness and lower microbiological content during post-harvest, thus demonstrating its influence in maintaining the physical characteristics of the banana that please the consumer.